Peningkatan Pemanfaatan Teknologi Informasi Dalam Jumpa Bakti Gembira Se-Kabupaten Jombang - Fajar Indra Kurniawan (Politeknik Kampar, 2024)
PMI Kabupaten Jombang organized the Jumpa Bakti Gembira Palang Merah Remaja (Jumbara PMR) competition across Jombang Regency, involving 543 participants from elementary, middle, and high school levels. The main problem was how to publish the results of 21 competition categories on the same day with accuracy and timeliness. To facilitate the organizing committee and participants in utilizing technology to speed up and enhance the accuracy of the competition results assessment. The research and development (R&D) method was used in the development of an information system that automatically processes the assessment and recapitulation of competition results, along with implementation support, ranging from system testing to training and score monitoring. The development of the information system successfully improved the efficiency of the competition assessment and recapitulation process. This system facilitated participants, the organizing committee, and judges in managing data, reducing the time required for data collection, and enhancing the accuracy and integrity of the results. The developed information system provided an effective solution to the problem of publishing competition results. The use of information technology has proven to increase the transparency and professionalism of PMI Kabupaten Jombang.